The Contribution of Parental Support to Student Learning Motivation - Purnomo, Dzulfa Idztihar; Yanah, Dewi; Merisanti, Merisanti (Asosiasi Asesmen Pendidikan (AAP), 2024)
The study aims how influential is the level of support provided by parents both at school and at home on the increase in learning motivation. This research is using method quantitative, with a correlational type. The respondents in this study consist of 76 student participants, investigating parental support and learning motivation The research will use simple linear regression to test the significance between parental support and learning motivation. This research using questionnaire with Likert Scale and the results are the reliability of the parental support questionnaire was 0.922. Meanwhile, the learning motivation questionnaire has a reliability of 0.726. The result show contribution of independent variable parental support (X) to dependent variable learning motivation (Y) is 23.1%. It implies that learning motivation is 23.1% influenced by parental support with the remaining 76.9% was influenced by other factors that are not included in this research.